Innate immune responses in hepatitis C virus‐exposed healthcare workers who do not develop acute infection. Issue 5 (30th September 2013) - Werner, Jens Martin; Heller, Theo; Gordon, Ann Marie; Sheets, Arlene; Sherker, Averell H.; Kessler, Ellen; Bean, Kathleen S.; Stevens, M'Lou; Schmitt, James; Rehermann, Barbara
Abstract : Hepatitis C virus (HCV) infection typically results in chronic disease with HCV outpacing antiviral immune responses. Here we asked whether innate immune responses are induced in healthcare workers who are exposed to small amounts of HCV, but do not develop systemic infection and acute liver disease. Twelve healthcare workers with accidental percutaneous exposure to HCV‐infected blood were prospectively studied for up to 6 months for phenotype and function of natural killer T (NKT) and NK cells, kinetics of serum chemokines, and vigor and specificity of HCV‐specific T‐cell responses. Eleven healthcare workers tested negative for HCV RNA and HCV antibodies. All but one of these aviremic cases displayed NKT cell activation, increased serum chemokines levels, and NK cell responses with increased CD122, NKp44, NKp46, and NKG2A expression, cytotoxicity (as determined by TRAIL and CD107a expression), and interferon‐gamma (IFN‐γ) production. This multifunctional NK cell response appeared a month earlier than in the one healthcare worker who developed high‐level viremia, and it differed from the impaired IFN‐γ production, which is typical for NK cells in chronic HCV infection. The magnitude of NKT cell activation and NK cell cytotoxicity correlated with the magnitude of the subsequent HCV‐specific T‐cell response. T‐cell responses targeted nonstructural HCV sequences that require translation of viral RNA, which suggests that transient or locally contained HCV replication occurred without detectable systemic viremia. Conclusion : Exposure to small amounts of HCV induces innate immune responses, which correlate with the subsequent HCV‐specific T‐cell response and may contribute to antiviral immunity. (Hepatology 2013;58:1621–1631)